Finger Clubbing Caused by Herbal Tea - Saifudin Rashiq; Neil E Brown; Richard N Fedorak (Canadian Respiratory Journal)
Clubbing of the fingers is often taken to be a sign of serious illness. Its discovery, particularly if there are associated symptoms in the cardiovascular, respiratory or gastrointestinal systems, usually leads to exhaustive investigation. A case is presented in which the etiology of clubbing was found only when a new history of heavy ingestion of herbal tea was obtained, extensive work-up having previously been unhelpful. Other cases appearing in the English-language literature are cited, some universal etiological associations are described, and an attempt is made to explain the phenomenon, based on a recent theory of the cause of clubbing.